The Operation and Model of UPQC in Voltage Sag Mitigation Using EMTP by Direct Method - S. Mehdi Hosseini (Emerging Science Journal, 2018)
Nowdays, regarding to the great us of sensitive devices, the quality of the transmitted power, have become an important issue. One of the most important dimension of power quality is magnitude load terminal voltage. Different devices has been designed for voltage sag compensation or other distortions. UPQC is a compensator which is able to compensate all distortions, such as voltage sag, flicker, unbalance, harmonic and current distortions such as reactive, harmonic and unbalance. Several controllers have been designed to compensate the whole or a part of distortions. In this paper its going to introduce a kind of controller which is able to compensate voltage sag to direct and simple by UPQC. At the end, simulation and voltage sag mitigation is going to be performed by ATP-EMTP software.